Safety and security in the age of global tourism - Kővári , István; Zimányi, Krisztina (Applied Studies in Agribusiness and Commerce, 2010)
Safety and security have always been indispensable condition for travel and tourism. Research and education also has to face the issues of security and safety in tourism in order to prepare future specialists of the industry by incorporating new results of research to academic curricula.